2019
DOI: 10.3390/s19194330
|View full text |Cite
|
Sign up to set email alerts
|

AR Enabled IoT for a Smart and Interactive Environment: A Survey and Future Directions

Abstract: Accompanying the advent of wireless networking and the Internet of Things (IoT), traditional augmented reality (AR) systems to visualize virtual 3D models of the real world are evolving into smart and interactive AR related to the context of things for physical objects. We propose the integration of AR and IoT in a complementary way, making AR scalable to cover objects everywhere with an acceptable level of performance and interacting with IoT in a more intuitive manner. We identify three key components for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…User study results demonstrated that for the maintenance purposes, augmenting the view with the actual readings from the sensor could be beneficial to simplify the distinction of the faulty sensors [63]. This is in line with the research of AR potentials in helping to carry out the tasks and interact with IoT objects [69]. The second prototype enriches the actual space with the digital objects that change their properties based on environmental conditions.…”
Section: State Visualizationsupporting
confidence: 63%
See 1 more Smart Citation
“…User study results demonstrated that for the maintenance purposes, augmenting the view with the actual readings from the sensor could be beneficial to simplify the distinction of the faulty sensors [63]. This is in line with the research of AR potentials in helping to carry out the tasks and interact with IoT objects [69]. The second prototype enriches the actual space with the digital objects that change their properties based on environmental conditions.…”
Section: State Visualizationsupporting
confidence: 63%
“…In addition to the basic dashboard, we have developed AR-based visualization with two prototypes. AR-based solutions promise richer user experience and they are used in various settings, like navigation, tourism, and education [68,69]. The first prototype that we developed demonstrates live sensor measurements when the phone camera is pointing to the particular sensor [63].…”
Section: State Visualizationmentioning
confidence: 99%
“…Firstly, the diversity in the use of AR and the affordance of IoT to provide rich data on agents' contexts form a fertile ground for developing new interaction modalities [16] and, consequently, new MI systems. Secondly, previous research has shown that a complementary combination of AR and IoT enables smart and interactive environments where the agent's interaction with IoT devices can become more intuitive [17], which is essential when designing interaction with complex artifacts and unfamiliar devices [18]. Thirdly, AR and IoT enable otherwise unperceivable information (e.g., readings from sensors, ratings of a service from other users) to be expressed through perceivable modalities (e.g., visualizations, sounds, vibrations) [16].…”
Section: Input Modalitiesmentioning
confidence: 99%
“…To solve this problem, the idea of using another interesting approach in non-model-based techniques, which is based on a learning-based descriptor in simultaneous localization and mapping (SLAM) is proposed. This descriptor can be trained using bootstrapping training method [96]. SLAM is conceptualized in robotics based on the idea that it is possible for a mobile robot to move in a completely unknown environment while mapping and localizing simultaneously [97,123].…”
Section: No-model-based Trackingmentioning
confidence: 99%